Crashworthiness behaviour of different laminate design of eco hybrid composite - Chong Jo-Ann, 1995-, author; Haris Ahmad Israr Ahmad, supervisor; Fakulti Kejuruteraan Mekanikal (Johor Bahru, Johor : Universiti Teknologi Malaysia, 2018)
Project Paper (Sarjana Muda Kejuruteraan (Mekanikal Aeronautik)) - Universiti Teknologi Malaysia, 2018